Factors from Underwriter That Influence Initial Return of The Companies Doing Initial Public Offerings in Indonesia Stock Exchange in The Period Of 2004-2011 - Ferry Sugianto; Liliana Inggrit Wijaya (Forum Manajemen Indonesia (FMI), 2014)
The objective of this study is to examine whether the underwriter’s factors affect the initial return of the companies that were going to do Initial Public Offerings (IPO). This study uses the quantitative approach using Ordinary Least Squares (OLS) method to examine whether the underwriter’s factors affect the initial return. The samples of this study are companies which are doing the IPO in Indonesia Stock Exchange in the period of 2004- 2011. This study finds that the underwriter’s factors have significant effect for the companies which do IPO, such as prestige, number of syndicate, experience, and oversubscription. But other independent variables like reputation, total assets, age, and price revision have no significant impact to initial return. The paper provides useful information for emitens how to choose good underwriters to avoid underpricing which causes wealth transfer to investors, the underwriters with good prestige, big syndicates, a lot of experiences, and less of doing oversubscription are recommended. Keywords: stock, initial return, underwriter, emiten, Initial Public Offerings.